2015
DOI: 10.1111/jon.12292
|View full text |Cite
|
Sign up to set email alerts
|

Histogram Analysis of Diffusion Tensor Imaging Parameters in Pediatric Cerebellar Tumors

Abstract: The 25th percentile for MD yields the best results for the presurgical differentiation between pediatric cerebellar pilocytic astrocytomas and medulloblastomas. The analysis of other DTI metrics does not provide additional diagnostic value. Our study confirms the diagnostic value of the quantitative histogram analysis of DTI data in pediatric neuro-oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…In this research, the skewness and kurtosis of medulloblastoma were higher than those of pilocytic astrocytoma. The skewness and kurtosis of ADC histograms significantly distinguished between pilocytic astrocytoma and medulloblastoma, which was consistent with the research results of Wagner et al [ 10 ]. Medulloblastomas were more heterogeneous.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this research, the skewness and kurtosis of medulloblastoma were higher than those of pilocytic astrocytoma. The skewness and kurtosis of ADC histograms significantly distinguished between pilocytic astrocytoma and medulloblastoma, which was consistent with the research results of Wagner et al [ 10 ]. Medulloblastomas were more heterogeneous.…”
Section: Discussionsupporting
confidence: 92%
“…Because both pilocytic astrocytoma and medulloblastoma have obvious cystic parts, ADC values cannot fully reflect the tumor condition, and it is unreliable to identify tumor types or grades by ADC value alone. The histogram can be used to analyze the whole tumor volume and is less dependent on the tumor microstructure and small sample of the region of interest (ROI) [ 10 ]. ADC histogram shows the frequency of ADC values and provides more descriptive information outside the average ADC value.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,[6][7][8] The purpose of our study was to analyze the volumetric voxelwise ADC histogram of solid components in intraaxial posterior fossa tumors involving the fourth ventricle, and apply the quantitative variables derived from ADC histogram analysis with other conventional imaging characteristics for differentiation of tumors based on pretreatment MRI. 9…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that histogram features extracted from DTI can characterize tumor heterogeneity and carry diagnostic values. 29 Every intratumoral voxel bears both isotropic and anisotropic diffusion information. Neither DTI-p nor DTI-q is sufficient to reflect the full tensor.…”
Section: Discussionmentioning
confidence: 99%